HUBUNGAN SANITASI LINGKUNGAN DENGAN KEJADIAN MALARIA DI WILAYAH KERJA PUSKESMAS MASNI KABUPATEN MANOKWARI - Mensiyana Alut; Misbahul Subhi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to determine the relationship between environmental sanitation and the incidence of malaria in the working area of Puskesmas Masni, Manokwari Regency. This research employed a quantitative approach with a cross-sectional design, where data were collected through field observations and structured questionnaires administered to respondents. The study population consisted of 96 individuals recorded as having malaria, with a sample of 49 respondents selected randomly. Data analysis was conducted using the chi-square test; however, since the test assumptions were not fully met—specifically, 6 cells (66.7%) had expected values less than 5—an alternative test, the likelihood ratio, was applied to obtain more accurate results. The analysis results showed a p-value of 0.007 (p < 0.05), indicating a significant relationship between environmental sanitation and malaria incidence. The study concludes that environmental sanitation conditions contribute to an increased risk of malaria, highlighting the need for environmental improvements and the consistent implementation of clean and healthy living behaviors as preventive measures.